(untitled) (Journal of Atomic and Molecular Sciences, 2017)
The ionization and high-order harmonic generation (HHG) of a hydrogen molecule in an ultra-short intense laser are investigated by using the time-dependent density functional theory (TDDFT). Our numerical results show, the higher ionization probability and lower cutoff energy of harmonic emission compared with those from the time-dependent Schrodinger equation (TDSE), which is caused by the smaller ionization energy from TDDFT. The disparities of the HHG transient behavior and the attosecond pulse are also discussed.